L’ambiente psichiatrico nell’opera di Franco Basaglia e Mario Tobino: verso un’ecologia delle idee (sulla follia) - Redaelli, Stefano (Studia Romanica Posnaniensia, 2022)
The aim of the article is to compare the reform and the narration of the psychiatric environment in the work of Franco Basaglia and Mario Tobino from an ecological perspective. Both psychiatrists worked to reform the asylum spaces and the therapeutic relationships within it. Their actions and their narrations were both ecological but had an opposite ending. While Tobino defended until the end the idea of a safe psychiatric environment, protected by society, considered dangerous, Franco Basaglia strongly affirmed the repressiveness of the asylum space, the need to dismantle it and return the madness to society.